Segment-interaction and its relevance to the control of movement during sprinting - Huang, L.; Liu, Y.; Wei, S.; Li, L.; Fu, W.; Sun, Y.; Feng, Y. (Journal of Biomechanics, 2013)
The aims of this study were to investigate the functions of muscle torque and its relation to other torque components during sprinting stance and swing phases. Three-dimensional kinematics and ground reaction force data were collected from eight elite male sprinters performing maximal-effort sprinting on a synthetic track. Intersegmental dynamics approach (ISD) was used to quantify lower extremity joint torque and their components during one gait cycle of the maximal speed phase during sprinting. Specifically, a modified version of the ISD was used to determine the relationship among the active muscle torque (MST), passive motion-dependent torque (MDT), ground reaction torque (EXT), gravitational torque (GTT), and net joint torque (NET) during stance and swing phases. The contribution of each torque component to lower extremity joint motion was quantified. Our results revealed that the active MST functioned to counteract EXT during stance phase. EXT acted to accelerate knee extension and hip flexion, meanwhile the muscles across these joints produced flexion torque at the knee and extension torque at the hip. During swing phase, MDT at the knee and hip joints was mainly produced by leg angular acceleration which was very significant at the moment when leg swing from forward to backward, active MST counterbalanced the effect of MDT. In summary, muscle torque functions mainly to push the ground to counter ground reaction force for controlling the movement during stance phase. However, the role of muscle torque changes during swing phase to mainly counteract the effect of MDT to control the movement direction of the lower extremity at both the hip and knee joints.